Cardiac shear wave elastography can distinguish healthy and scarred myocardium in patients with conduction delays. (14th October 2021) - Wouters, L; Duchenne, J; Bezy, S; Papangelopoulou, K; Puvrez, A; Klop, B; Voros, G; D'hooge, J; Voigt, J U
Abstract: Background: Cardiac resynchronization therapy (CRT) is an established therapy for patients suffering from heart failure and left bundle branch block (LBBB) conduction delays. Despite its proven beneficial effects, CRT is associated with a high percentage of non-response. Since CRT has shown to be less effective in patients with ischemic cardiomyopathy, determining the presence of myocardial scar before implantation could help to improve the response-rate. However, the gold standard to assess myocardial scar, magnetic resonance imaging (MRI), cannot be used in every patient, due to already implanted devices and/or reduced renal function. Recently introduced shear wave elastography (SWE) allows the non-invasive assessment of myocardial stiffness. Natural shear waves are excited by mitral valve closure (MVC) and travel through the heart with a speed directly related to tissue stiffness. SWE has previously been proven to be able to detect myocardial scar, however this has never been shown in the presence LBBB. Purpose: The aim of this study was to evaluate the capability of SWE as a novel method to determine myocardial scar in patients with conduction delays. Methods: We included 24 heart failure patients (age: 68±10; 50% males) with ischemic (n=8) and non-ischemic (n=16) cardiomyopathy. The CRT device was set to AAI mode in order to obtain native ventricular conduction. For patients with ischemic cardiomyopathy, the presence and location of scar was determined by MRI or scintigraphy. All ischemic patients had septal scar only. For SWE, left ventricular parasternal long-axis views were acquired with an experimental high frame rate ultrasound scanner (average frame rate: ±1200 Hz). Shear waves were visualized in M-modes of the septum, colour coded for tissue acceleration. The slope of the shear waves in the M-mode represents their propagation speed (Figure A). Results: There was no significant difference between the ischemic and non-ischemic patients in QRS width after CRT (149±31 ms vs 144±26 ms), systolic blood pressure blood pressure (135±11 mmHg vs 135±23 mmHg), diastolic blood pressure (74±9 mmHg vs 70±11 mmHg) and heart rate (58±4 bpm vs 63±9 bpm) (all p>0.05). Ejection fraction (33±8% vs 45±10%), end-diastolic volume (196±34 ml vs 129±64 ml) and global longitudinal strain (−9.8±3.1% vs −14.1±4.1%) differed significantly between the groups (all p<0.05). Shear wave speed after MVC was significantly higher in patients with septal scar compared to non-ischemic patients (8.2±1.9 m/s vs 5.5±1.2 m/s; p<0.01) (Figure B). Conclusion: In the presence of scar, we found markedly elevated shear wave propagation speed compared to non-ischemic patients. These results indicate that SWE is able to identify scarred myocardium even in patients with LBBB. We therefore believe that SWE could be a novel easy and non-invasive method to evaluate septal myocardial scarring in patients before CRT implantation. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWO - Research Foundation Flanders